Differential Effects of Weight Status on the Relations Between Diet Quality, Socioemotional Development, and Academic Performance in U.S. Schoolchildren (P14-008-19). (13th June 2019) - Chiu, Dorothy; Wang, Youfa; Riley, Anne; Hurley, Kristen
Abstract: Objectives: Child obesity, a risk factor for adverse health and functioning, can foster a heightened stress state in the body that may affect relations between nutritional status and cognitive development. We investigated if associations between diet quality (DQ), socioemotional development (SED), and academic performance (AP) varied by child weight status in U.S. 5 th graders. Methods: Nationally representative data from 7755 U.S. children (mean age 11–11.5 years) were analyzed using survey-weighted, multiple linear regression models adjusted for relevant factors. DQ was calculated by applying a novel short Diet Quality Index ( s DQI) on a brief food frequency questionnaire. Established measures for SED ( Self-Description Questionnaire scaled scores for internalizing and externalizing problem behaviors [IPB, EPB] and peer relations competency) and AP (standardized reading, math, and science test scores) served as dependent variables. Children's weight status was classified based on their BMI compared against sex-age-specific BMI percentiles of CDC Child Growth Charts. Results: Some relations between DQ and SED and AP were slightly moderated by child weight status. A borderline significant interaction between DQ and IPB (overall F = 2.48; P = 0.06) revealed better socioemotional health with higher diet quality for both underweight (β = −0.02 [SE = 0.01]; P < 0.01) and overweight children (β = −0.01 [SE = 0.00]; P = 0.01) that was not observed in children of normal weight (β = −0.00 [SE = 0.00]; P = 0.07) or obese (β = −0.01 [SE = 0.00]; P = 0.16) status. Another borderline significant interaction between DQ and math scores (overall F = 2.39; P = 0.07) highlighted higher scores with higher diet quality in underweight (β = 0.18 [SE = 0.07]; P = 0.01) and normal weight children (β = 0.10 [SE = 0.02]; P < 0.01) not observed in overweight (β = 0.00 [SE = 0.04]; P = 0.96) or obese (β = 0.02 [SE = 0.05]; P = 0.75) children. Significant interactions were not observed between DQ and EPB or peer relation competency, or DQ and reading or science scores, by child weight status. Conclusions: The moderating effects of child weight status here underscore a need for more research on the stress of malnutrition (non-normal weight status) in child development. Interventions to improve cognitive health through diet should heed underlying vulnerabilities within population groups to optimize success. Funding Sources: n/a.